A readability analysis of the JBLFMU's worktext in communication skills I - Hampac, Shirley G (Iloilo City, Philippines University of the Philippines Visayas, 2013)
This study used the Fry Readability Graph to look into the Worktext readability level and the teachers' and students' assessment to determine its readability features and characteristics, respectively. It further looked into the patterns f results, and the framework for revision as a result of the investigation.The study employed the simple random sampling to determine the student respondent but used the purposive sampling for the teachers. The statistical instruments used to organize the descriptive data were the frequency count, percent, mean and ranking. For the inferential data, the Mann-Whitney U was employed. The result reveal that the Worktext has an average readability of 13, a level suitable for third year college students. Hence it is not readable for the target-readers- the firsat year college students. The teachers' composite rating taking all features of readability of the Worktext is adequate but merely passable. O the other hand, the students' composite rating of the Worktext is appropriate but falls short of meeting the criterion. The study further shows that there is a significant difference between ratings of two groups of students of the Worktext readability when they were grouped according to academic status. The result of the readability analysis of the Fry Graph formula and the assessment of the teachers and students show the need for revision or improvement of the Worktext for better readability.
Special Problem (M.Ed-English as a Second Language) -- Iloilo City : U.P. Visayas, June 2013.